Mental Imagery And Performance Improvement Of Basketball Athletes In The 16-18 Year Age Group - et.al, Fakhri Fajrin Kurniawan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to determine whether there was a relationship between mental imagery and performance improvement of basketball athletes in the 16-18 year age group. This study used quantitative research methods. The research sample consisted of 30 basketball athletes in the Cirebon area using the purposive sampling technique. The research instrument used mental imagery training and an athlete's performance improvement scale developed according to the needs. The result showed the value r count for correlation Mental Imagery with Athlete’s performance improvement was 0.853 > r table 0.361. So it could be concluded that there correlation between mental imagery with Basketball athlete’s performance improvement in the 16 until 18 year age group. The result suggests that the higher the mental imagery, the higher the performance improvement in basketball athletes in the 16 until 18 year age group and vice versa.